Prevalence, antibiotic susceptibility, and genetic diversity of Salmonella, Campylobacter, and Escherichia coli O157:H7 collected at four Kansas beef cattle feedyards over 13 months - D.R. Hyatt; J.C. Galland; S. Crupper; L. Hawkins; N.V. Anderson; Gerald L. Stokka (Kansas Agricultural Experiment Station Research Reports, 1998)
Salmonella, Campylobacter, and Eschericia coli O157:H7 are important foodborne pathogens, but longitudinal studies of their prevalence in beef cattle feedyards have not been done. Our long- term study involved 24,556 samples taken from beef cattle feedyards found overall prevalence's of 4.87% for Salmonella, 20.1% for Campylobacter in hospital pen fecal samples, and 0.20% for E. coli O157:H7. Yard and pen differences (P<0.05) were detected. All 53 E. coli O157:H7 isolates were resistant to Talmicosin and Erythromycin, two antimicrobials used in food animal medicine. Their genetic diversity was high and did not indicate the presence of resident strains at the yards studied. Salmonella, Campylobacter, and E. coli O157:H7 were probably brought into the yards by shipments of new cattle. Many of these organismswere susceptible to antibiotics commonly used to treat beef cattle.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Bacterial infection; Salmonella; Campylobacter; E. coli O157:H7; Feedyards; Antibiotic susceptibility